2020
DOI: 10.3139/120.111583
|View full text |Cite
|
Sign up to set email alerts
|

Taguchi optimization of surface roughness in grinding of cryogenically treated AISI 5140 steel

Abstract: This study investigated the performance of the grinding parameters used in the cylindrical grinding process of AISI 5140 steel and identified optimum grinding conditions via the Taguchi optimization method. Experiments were carried out via the L18 orthogonal array. Control factors for optimum surface roughness (Ra) values were determined by using the Taguchi method. Two different grinding wheels (SiC and Al2O3), three different cryogenic samples (CHT, DCTT-15 and DCTT-30) and depth of cuts (100, 200 and 300 μm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…where n is the number of data of the experiment and y i is the measured data at the ith experiment [24]. In addition to the signal-to-noise ratio, a statistical analysis of variance (ANOVA) was employed to demonstrate the impact of process parameters on surface roughness.…”
Section: Taguchi Methodmentioning
confidence: 99%
“…where n is the number of data of the experiment and y i is the measured data at the ith experiment [24]. In addition to the signal-to-noise ratio, a statistical analysis of variance (ANOVA) was employed to demonstrate the impact of process parameters on surface roughness.…”
Section: Taguchi Methodmentioning
confidence: 99%
“…To address these challenges, scholars have focused on the research of robotic abrasive belt grinding force/position control [8][9][10][11][12], parameter optimization [13][14][15], compensation control [16,17], etc. Xu et al [18,19] proposed a robotic belt grinding force control method that combines force/position compound control with PI/PD control, and analyzed the precision, stability and reliability of the system.…”
Section: Introductionmentioning
confidence: 99%
“…Kara et al. [12] have investigated the performance of the grinding parameters used in the cylindrical grinding process of cryogenically treated AISI 5140 steel and the results showed that optimal average surface roughness values were obtained on specimens cryogenically treated for 30 h. Therefore, a comprehensive understanding of the microstructure evolution of hot work tool steels during DCT is significant.…”
Section: Introductionmentioning
confidence: 99%